Implementasi public relation di New Daily Laundry dalam meningkatkan keterampilan komunikasi kepada pelanggan - Ayu, Diyah Isthi (Maliki Interdisciplinary Journal, 2023)
This research aims to determine the implementation of Public Relations in an MSME, namely the New Daily Laundry MSME as a provider of dry cleaning and ironing services. This research uses qualitative research methods by conducting observations at New Daily Laundry. Public Relations practices at New Daily Laundry are in the form of providing services to customers, both those who come to deliver clothes to be washed and those who pick up clothes that have been washed. Communication sessions in serving customers occur when the customer arrives, the service provider will greet them. However, in this observation of course there were also several obstacles, such as it being difficult to distinguish slips for customers from slips that would be archived by the laundry owner, and practical activities had not been carried out completely by themselves, so they were still assisted by the laundry owner.